Prognostic impact of EGFR and KRAS mutations in lung cancer survival during pre-tki era: the real scenario at a cancer public center of reference in Brazil - Thais Abreu Almeida; Jeanine Marie Nardin; Amanda Jurgensen; Janaina Takahashi; Juliana Jung; Graziele Losso; José C. Casali-da-Rocha (Brazilian Journal of Oncology)
Objective: To evaluate the genetic tests is fundamental for the adequate treatment of non-small cell lung cancer (NSCLC) with tyrosine kinase inhibitors (TKI). Given that access to this evaluation is still limited for those who depend on the Brazilian Public Health System, it seems important to provide regulatory agencies with epidemiological and prognostic information to guide future health policies and guidelines in Brazil. This work aims to characterize EGFR and KRAS mutations in NSCLC and associating them with patients demographic and tumor clinical-pathologic features. Methods: From 2004 to 2017, 237 metastatic NSCLC patients treated at Erasto Gäertner Cancer Hospital were included in this study. Electronic medical records were retrospectively reviewed and the mutational status EGFR and KRAS were defined. Results: We detected EGFR mutation in 20 samples (15.7%), and KRAS mutation in 26 samples (21.5%). The majority of EGFR mutations was detected within the exon 19 (n=9, 45.0%), and for KRAS G12V (n=8, 30.8%) and G12C (n=8, 30.8%) were the hotspots. The median overall survival was 11 months. We did not detect any statistical differences in survival rates between mutated and wild-type tumors neither for EGFR (p=0.898) nor for KRAS (p=0.458). Only two patients had access to TKI and were considered outliers with the best survival rates. Conclusion: We described important information about NSCLC biological behavior in a population treated in a reference public cancer center in South Brazil. Studies like this highlight the magnitude that TKI treatment could have in the overall survival of patients with NSCLC after being introduced into the SUS. Future studies that address the economic impact of this issue are also needed. Here we also make a comparison of our results with other regions of Brazil that have different genetic backgrounds to evaluate the impact of targeted therapies.